2020
DOI: 10.1103/physrevlett.125.097005
|View full text |Cite
|
Sign up to set email alerts
|

Using Uniaxial Stress to Probe the Relationship between Competing Superconducting States in a Cuprate with Spin-stripe Order

Abstract: We report muon spin rotation and magnetic susceptibility experiments on in-plane stress effects on the static spin-stripe order and superconductivity in the cuprate system La 2−x Ba x CuO 4 with x ¼ 0.115. An extremely low uniaxial stress of ∼0.1 GPa induces a substantial decrease in the magnetic volume fraction and a dramatic rise in the onset of 3D superconductivity, from ∼10 to 32 K; however, the onset of at-least-2D superconductivity is much less sensitive to stress. These results show not only that largev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 39 publications
(46 reference statements)
4
33
0
Order By: Relevance
“…In the absence of strain, bulk susceptibility measurements suggest an onset of 2D superconducting correlations, along with spin-stripe order, near 40 K; however, the spin-stripe order is weaker than at x = 1/8 so that 3D superconducting order develops below ∼12 K [5]. Application of significant in-plane stress causes the bulk superconducting T c to rise to 32 K, while muon-spin-rotation spectra indicate a reduction in the magnetically ordered volume fraction by more than 50%, consistent with a decrease in the volume of spin-stripe order and associated PDW order [96]. While the dominant character of the superconducting state changes under strain, the onset temperature of superconducting coherence changes relatively little.…”
Section: Pdw Vs Uniform D-wave Superconductivitymentioning
confidence: 86%
See 1 more Smart Citation
“…In the absence of strain, bulk susceptibility measurements suggest an onset of 2D superconducting correlations, along with spin-stripe order, near 40 K; however, the spin-stripe order is weaker than at x = 1/8 so that 3D superconducting order develops below ∼12 K [5]. Application of significant in-plane stress causes the bulk superconducting T c to rise to 32 K, while muon-spin-rotation spectra indicate a reduction in the magnetically ordered volume fraction by more than 50%, consistent with a decrease in the volume of spin-stripe order and associated PDW order [96]. While the dominant character of the superconducting state changes under strain, the onset temperature of superconducting coherence changes relatively little.…”
Section: Pdw Vs Uniform D-wave Superconductivitymentioning
confidence: 86%
“…The close relationship between the PDW and uniform superconducting orders is illustrated by a study of the phase transitions in LBCO x = 0.115 as a function of uniaxial strain [96]. In the absence of strain, bulk susceptibility measurements suggest an onset of 2D superconducting correlations, along with spin-stripe order, near 40 K; however, the spin-stripe order is weaker than at x = 1/8 so that 3D superconducting order develops below ∼12 K [5].…”
Section: Pdw Vs Uniform D-wave Superconductivitymentioning
confidence: 89%
“…Additional support for the competition scenario is the observation of enhancement of the elastic IC response on application of an external magnetic field perpendicular to the CuO 2 planes, indicating that suppression of the superconducting order goes hand-in-hand with a strengthening of the magnetic order [17,[20][21][22][23][24][25][26]. The other way around, it was recently demonstrated that suppression of magnetic order by strain leads to a dramatic increase in T c in LBCO [27].…”
Section: Introductionmentioning
confidence: 88%
“…The 1/8 anomaly is a phenomenon where the T c is suppressed at x = 1/8. The suppression of T c at x = 1/8 was proposed due to the incommensurate magnetic ordering [20][21][22][23][24]. This was linked to the stripe theory in which the spin domain and hole domain are self-organized in the CuO 2 plane [20,22,24].…”
Section: Introductionmentioning
confidence: 99%
“…The suppression of T c at x = 1/8 was proposed due to the incommensurate magnetic ordering [20][21][22][23][24]. This was linked to the stripe theory in which the spin domain and hole domain are self-organized in the CuO 2 plane [20,22,24]. In the case of ferromagnetic spin fluctuation, it was predicted to occur in a highly over-doped regime at x > 0.25 causing the suppression of superconductivity in this regime [25,26].…”
Section: Introductionmentioning
confidence: 99%